Isolated Sporothrix schenckii Monoarthritis - Aram Barbaryan; Wissam El Atrouni; Stefania Bailuc; Matthew W. Jones; Maharshi Bhakta; Khaldoun Haj Mahmoud; Aibek E. Mirrakhimov (Case Reports in Infectious Diseases)
Sporothrix schenkii sensu lato is a rare cause of arthritis. Its course is indolent with lack of constitutional symptoms resulting in delayed presentation and diagnosis. It is a dimorphic fungus found ubiquitously in sphagnum moss, decaying vegetation, soil, and hay. Inoculation of dirt into the skin and soft tissues and, in rare instances, inhalation of aerosolized conidia from soil and plants can lead to infection. Subacute and chronic involvement of skin and subcutaneous tissues is the most common manifestation of sporotrichosis in immunocompetent hosts. In patients with underlying risk factors (HIV, alcoholism, diabetes mellitus, organ transplant patients, immunosuppressive medications, steroids, and malignancies), it can often have disseminated visceral, osteoarticular, meningeal, and pulmonary involvement. Sporothrical arthritis most commonly infects knee joint followed by hand and wrist joints. A culture of Sporothrix schenkii sensu lato is the gold standard for the diagnosis of sporotrichosis. Itraconazole is the drug of choice for osteoarticular sporotrichosis. We present a case of sporotrichal arthritis in a patient without skin or lymph node involvement who underwent treatment with itraconazole resulting in resolution of his symptoms.